Modern Mycobacterium Tuberculosis Strain in Bronchoalveolar Lavage from Tuberculosis Patients Associated with Lung Tissue Damage Severity - Budi Yanti1 , Muhammad Amin2 , Ni Made Mertaniasih2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: The Beijing sublineage modern Mycobacterium tuberculosis strain is the most dominantstrain in regards to causes of disease progression, extensive lung tissue damage, drug resistance and highoutbreak rates.Methods: Mycobacterium tuberculosis isolates were obtained from Bronchoalveolar lavage patients withactive pulmonary Tuberculosis before obtaining anti-tuberculosis drug treatments. The degree of severity ofparenchymal lung damage is classified by the NICE Scoring System. PCR was performed on DNA extractedfrom bronchial lavage, using primers targeting gene TbD1.Result: 30 active pulmonary tuberculosis patients were analyzed in this study. 13 isolates of modern strainsand 17 isolates of ancient strains were detected. In modern strains, 4 (30.8%) subjects had mild lung degreedamage, while 9 (69.2%) subjects had severe lung damage. In ancient strains, 12 (70.6%) subjects hadmild lung damage and 5 (29.4%) subjects had severe lung damage. Mycobacterium tuberculosis of modernstrains correlated with the degree of lung damage, p <0.05. Odds Ratio = 5.4 CI 95% (1,12-116,99).Conclusion: In Surabaya, modern strains of Mycobacterium tuberculosis were detected in BAL oftuberculosis patients. Radiograph evaluations revealed severe lung tissue damage. The risk of severe lungdamage with modern strains is 5.4 times higher than compared to ancient strains.